Eskatologi dalam Injil Markus - Nurnilam Sarumaha (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2017)
This article discusses the eschatology (end times) in the perspective of the Gospel of Mark. This topic is not contained in the other chapters in the book of Mark, rather than just in Mark 13: 1-37. Mark 13: 1-37 , featuring a view of the history in which the crisis and persecution at this age will pave the way for a future. It draws from the passage is an introduction to the understanding of eschatology, beginning with the statement of a disciple of Jesus about the temple (13:1) and the response of the Lord Jesus spoke of the events still in the future (eschatology) and at the same time talking about events imminent (the collapse of the temple). Both events are discussed simultaneously, as if the two events occur at the same time. In this paper, the two events referred to as a dual prophecy of the Lord Jesus. In Mark 13, the Lord Jesus spoke of the end of world history has begun. The period between the sufferings and death of Jesus until His coming the second time is the final phase of the history of the old times, before the start of a new era that is, when the Son of Man comes in all his glory. The phase between the two ages was marked by signs or events, both general and specific nature